Mandarin as foreign language: interactive courseware to enhance learning motivation and language proficiency / Hoe Foo Terng, Tan Teow Ghee and Lim Teck Heng - Hoe, Foo Terng; Tan, Teow Ghee; Lim, Teck Heng (2010)
This study attempts to examine the use of an interactive courseware in enhancing learning motivation and language proficiency among a group of elementary learners of Mandarin at UiTM Pulau Pinang. The courseware is developed by the researchers based on the current syllabus. The subjects in the study comprised two classes of Mandarin Level II diploma students. The experimental class adopted the use of interactive courseware and the control group used the printed workbook. Both groups were placed in classrooms that have similar facilities and taught by the same instructor who used the same content. At the end of the fourteenth week experimental intervention, the feedback obtained from a motivational questionnaire, the students’ final semester examination results, and a survey interview were analysed to find out the students’ inclination and acceptance on the use of interactive courseware. The experimental and control class students were also asked to write reflection regarding their acceptance towards using interactive courseware. The results obtained showed that there is no significant difference in the achievement between the groups. Though the students liked using the courseware and found it beneficial, those who did not own a personal computer claimed that it is a hassle as they needed to find / use a computer every time they want to do / revise the exercises. This had somehow affected their motivation to learn. Another interesting discovery is most of the students preferred to obtain the answers from their instructor instead of looking for the answers on their own. This indicated the students are not self-directed learners and are still very much dependent on the instructors.